1977
DOI: 10.1128/jb.131.2.662-671.1977
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of lipid bodies in Tilletia caries teliospores

Abstract: The ultrastructure of lipid bodies within developing, dormant, and germinating Tilletia caries (DC.) Tul. (race T-16) teliospores was studied by freezeetching and thin-sectioning techniques. When teliospores were prefixed in sodium cacodylate-buffered glutaraldehyde-acrolein for 24 h before further processing, most of the lipid bodies appeared to have a uniformly osmiophilic matrix. Some of these lipid bodies were surrounded by thin electron-dense lines that appeared to be half-unit membranes. Occasionally thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Ultrastructural and chemical studies of teliospores of T. tritici and T. controversa have shown that lipid bodies are a major part of the spore (5,6,14). Weber and Trione (19) found that T. tritici lipid was mainly in the form of FFAs which were converted to methyl esters during initiation of germination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrastructural and chemical studies of teliospores of T. tritici and T. controversa have shown that lipid bodies are a major part of the spore (5,6,14). Weber and Trione (19) found that T. tritici lipid was mainly in the form of FFAs which were converted to methyl esters during initiation of germination.…”
Section: Discussionmentioning
confidence: 99%
“…In other dormant fungal spores, the scarcity of membranes results in a low amount of phospholipids (9). While membranes are relatively scarce in dormant teliospores (5,6,7), differences in phospholipids and other membrane lipids should be examined. We are currently exploring this and the production of FFAs during hydration and early germination of teliospores.…”
Section: Discussionmentioning
confidence: 99%